Effect of Onion Powder in Diets of J.Quail on Serum Antioxidant Properties and Carcass Traits: - Pathakamuri, Kavitha; Bommireddy, Sravani; Dhulipalla, Srinivas Kumar; K, Naga Raja Kumari (Indian Journal of Animal Nutrition, 2023)
An experiment was carried out to assess the incorporation of onion powder (OP) in diets of J.Quail on serum biochemical parameters, liver function antioxidant properties and meat quality. Day old quail chicks (N=150) were randomly allotted into five treatment groups each with four replicates of ten birds. Experimental diet was prepared by incorporation of OP at 0, 0.5, 1.5 and 2 percent levels, and made isocaloric and iso nitrogenous rations and fed for a period of 5weeks. At the end of 5th week blood was collected from two birds per replicate and serum was analysed. At the end of the trial two birds per replicate a total of 30 birds were slaughtered to assess the carcass traits. Results of this study indicated that significant decrease in serum cholesterol, triglycerides, LDL-C, VLDL-C and significant increase in HDL-C with increase in OP in diet from 0.5 to 2%. A significant increase in superoxide dismutase activity and decrease (P<0.01) in malondiabldehyde activity was noticed with increase in OP in diet. Whereas, carcass traits were not influenced by incorporation of OP in diets. Basing on the results it can be concluded that OP can be incorporated safely up to 2% level without any adverse effects on liver, oxidative damage of meat as well as carcass traits.